Eriocaulaceae endémicas del Perú - Monsalve, Christhian (2006)
The family Eriocaulaceae is represented in Peru by five genera and 21 species of herbaceous plants (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Here we recognize five endemic species in two genera. We assigned IUCN threat categories to three species. Peru’s endemic Eriocaulaceae are found in grasslands of the Humid and Dry Puna, and Humid Montane Forest regions, between 1840 and 2600 m elevation. None of these taxa have been reported to occur within the country’s protected areas network.